MRPII and its applications / Ahmad Joraimee Mohamad and Nazrin Zakaria - Mohamad, Ahmad Joraimee; Zakaria, Nazrin (1996)
MRPII 2 has already being introduced in the early 70' s. In 1993, ICI Paints Malaysia as the first Malaysia's company, chose MRPII as their business philosophy. After 3 years implementing MRPII, ICI Paints successfully achieved MRPII Class A which was awarded by Oliver Wight himself, the man who introduced MRPII. Objectives: 1. To study and analyse the MRPII management concept in ICI Paints. 2. To collect as much as possible about MRPII implementation in ICI Paints. 3. To evaluate the results in MRPII implementation in ICI Paints.